Analysis of the Influence of Return on Equity and Earnings Per Share on the Stock Prices of Energy Sector Companies (Idxenergy) During the Windfall Profit Period 2021-2024 - Aswa Yuditkha Putra; Yeni Rafika Nengsih (Journal Research of Social Science, Economics, and Management, 2025)
The increase in energy commodity prices on a global scale in 2021-2024 has caused a windfall profit phenomenon that creates dynamics among investors on the Indonesia Stock Exchange regarding the relevance of fundamental metric signals to stock prices. This study was conducted to re-examine the effect of Return on Equity (ROE) and Earnings Per Share (EPS) on the share price of energy sector companies (IDXENERGY) by applying external control variables in the form of average coal prices. This study uses a quantitative approach with data analysis techniques in the form of panel data regression with a total of 172 observations. The analysis was conducted using a Fixed Effect Model (FEM) which was estimated using Clustered Standard Errors (by-Cross-section) in the EViews 13 application to ensure that the research results were free from heteroscedasticity and autocorrelation. The results of the study show that ROE has no significant effect on stock prices while EPS has a positive and significant effect on stock prices, making EPS relevant for investors in assessing the company's fundamental performance. These findings indicate that investors tend to act rationally and apply different treatment between transitory profits and fundamental profits.